On-field high-resolution quantification of the cobalt fraction available for bio-uptake in natural waters using antifouling gel-integrated microelectrode arrays. (April 2023) - Layglon, Nicolas; Creffield, Sébastien; Bakker, Eric; Tercier-Waeber, Mary-Lou
Abstract: We report the optimization, characterization, and validation of Adsorptive Square Wave Cathodic Stripping Voltammetry on antifouling gel-integrated microelectrode arrays for autonomous, direct monitoring of cobalt(II) metal species. Detection is accomplished by complexation with an added nioxime ligand. The limit of detection established for a 90 s accumulation time was 0.29 ± 0.01 nM in freshwater and 0.27 ± 0.06 nM in seawater. The microelectrode array was integrated in a submersible probe to automatically dose the complexing agent nioxime and realize an integrated sensing system. For the first time ever, the potentially bioavailable Co(II) fraction was determined in La Leyre River-Arcachon Bay continuum, enabling to evaluate the potential ecotoxicological impact of freshwater-carried Co(II) in the Arcachon Bay. The measured potentially bioavailable Co(II) concentrations were hazardous for aquatic biota along the continuum. The electrochemical Co(II) data were compared to ICP-MS data in various fractions to determine spatial Co(II) speciation. Graphical abstract: Unlabelled Image Highlights: Optimization, characterization, and validation of Ad-SWCV on GIME On-board detection of the bioavailable fraction of Co Spatial variation of the bioavailable Co species is site dependent. Small colloids and particles influence Co speciation. Bioavailable and dissolved Co concentrations surpassed ANZECC 99 % trigger value.